Study on friction and wear of preform Z‐directional fiber. Issue 5 (28th March 2022) - Guo, Zitong; Shan, Zhongde; Huang, Jihua; Wang, Dong; Huang, Hao; Xue, Debo; Hou, Zhuojian
Abstract: In order to reduce the wear and tear of Z‐yarn implantation into the preform, the frictional behavior of Z‐yarn during implantation into the preform was studied. According to the actual implantation conditions of Z‐yarns, we designed a guiding array clamping device and a tensile force sensor to study the changes of tensile strength of Z‐yarns at different implantation positions and implantation times, results show that the tensile strength of Z‐yarns decreases significantly after 25 implantations at the position of 4 N friction force, and it's necessary to replace Z‐yarns in time to avoid their fracture in the preform. The use of unadulterated solvent dimethyl silicone oil applied to the Z‐yarns, can significantly reduce their wear, the tensile strength of Z‐yarns after 60 implantations is only 5.6% lower than that of Z‐yarns after 10 implantations. Design the tension control system, and when the tension is 0.46 N, the tensile strength of Z‐yarns during implantation is 34.2% higher than without tension. Meanwhile, the relationship between the normal force applied to Z‐yarn and the implantation length and fiber bundle width are established by combining Hertzian theory and experimental data, and the friction coefficient algorithm during Z‐yarn implantation is derived by combining Howell's equation, which solves the problem that the fiber friction coefficient cannot be measured due to the complicated working condition of Z‐yarn implantation. The frictional wear mechanism of yarn during Z‐yarn implantation into the preform is revealed, and a method to reduce yarn wear and increase its continuous implantation number is proposed.